STUDENTS' PERCEPTIONS OF USING DEBATE IN SPEAKING AT SMA NEGERI 1 KOTA JAMBI - Hasibuan, Grace Patricia; Volya, Duty; Habizar, Habizar (JELT (Jambi-English Language Teaching), 2025)
This research aimed to determine students' perceptions of the use of debate in speaking as well as to determine students' difficulties in debate. The research participants consisted of five students who participated in English debate club at SMA Negeri 1 Jambi City. This research used a descriptive qualitative research design that aims to provide an understanding of students' perceptions and experiences related to the use of debate and the difficulties it faces. The results showed that students gave a positive perception and felt that the use of debate was effective in improving their speaking skills because debate encouraged them to continue practicing, so as to develop their vocabulary, pronunciation, fluency, and comprehension. However, students also have difficulties when debating, such as: defending the arguments, control emotion while debating, problem in listening skills, find or hear unfamiliar vocabulary, compose the sentence correctly. Overall, this research reveals that the use of debate has good benefits for students' speaking skills, but still needs to be supported by adequate training and coaching to overcome the difficulties experienced by students.